Reviews of recent publications (Studies in 20th & 21st Century Literature, 2008)
Fuentes, Carlos. Christopher Unborn by Asela Laguna Faber, Sebastian. Exile and Cultural Hegemony: Spanish Intellectuals in Mexico, 1939-1975 by Miguel González-Abellás Haines, Brigid and Margaret Littler. Contemporary Women’s Writing in German: Changing the Subject by Anna K. Kuhn Cate Arries, Francie. Spanish Culture behind Barbed Wire: Memory and Representation of the French by Carmen Moreno-Nuño Tremblay, Rosaline. L’Écrivain imaginaire, Essai sur le roman québécois, 1960-1995 by Betty Louise McLane-Iles Ponomareff, Constantin V. One Less Hope: Essays on Twentieth-Century Russian Poets by Maria Khotimsky
Keywords: Carlos Fuentes; Christopher Unborn; Asela Laguna; Sebastian Faber; Exile and Cultural Hegemony: Spanish Intellectuals in Mexico 1939-1975; Miguel González-Abellás; Brigid Haines; Margaret Littler; Contemporary Women’s Writing in German: Changing the Subject; Anna K. Kuhn; Francie Cate Arries; Spanish Culture behind Barbed Wire: Memory and Representation of the French; Carmen Moreno-Nuño; Rosaline Tremblay; L’Écrivain imaginaire Essai sur le roman québécois 1960-1995; Betty Louise McLane-Iles; Constantin V. Ponomareff; One Less Hope: Essays on Twentieth-Century Russian Poets; Maria Khotimsky